2020
DOI: 10.4315/0362-028x.jfp-19-372
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin–Producing Escherichia coli Contamination of Raw Beef and Beef-Based Ready-to-Eat Products at Retail Outlets in Pretoria, South Africa

Abstract: A cross-sectional study was conducted to determine the prevalence of and factors associated with Shiga toxin–producing Escherichia coli (STEC) in raw beef and ready-to-eat (RTE) beef products sold in 31 retail outlets in Pretoria, South Africa, and nearby areas. A total of 463 beef and RTE samples were screened for four STEC virulence genes (stx1, stx2, eaeA, and hlyA) and seven O-serogroups (O113, O157, O26, O91, O145, O111, and O103) with a multiplex PCR assay. The total aerobic plate count (TAPC) per gram w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Escherichia coli O150:H2 is not often found as contaminating agent in foods and environments, although it has been described as an emerging serogroup for over several years (Monaghan et al, 2012;Onyeka et al, 2020). The group of 21 closely resembling STECs from our study showed closest relationship with strains belonging to phylogroup B1, the group to which E. coli O104:H4 strains belong to.…”
Section: Discussionsupporting
confidence: 48%
“…Escherichia coli O150:H2 is not often found as contaminating agent in foods and environments, although it has been described as an emerging serogroup for over several years (Monaghan et al, 2012;Onyeka et al, 2020). The group of 21 closely resembling STECs from our study showed closest relationship with strains belonging to phylogroup B1, the group to which E. coli O104:H4 strains belong to.…”
Section: Discussionsupporting
confidence: 48%
“…Reducing foodborne pathogens (from any source) promotes food chain integrity, with Escherichia and Clostridioides reported as being amongst the most concerning from a One Health perspective [ 82 , 88 ]. Additionally, as these species are potentially toxicogenic, synthesised toxins may travel to distal sites of the host organism and remain in meat products postprocessing [ 5 , 44 , 68 , 71 ]. As such, any reduction in their prevalence should be viewed as a positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…DNA template from the broth enriched samples was prepared using QIAamp DNA Stool Mini Kit (Qiagen, Hilden, Germany) according to manufacturer's instructions. The DNA templates were investigated for the presence of stx 1 , stx 2 , eaeA , and ehxA genes using an mPCR method (Paton & Paton, 1998), conducted as previously described (Onyeka et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Suspect colonies were streaked on nutrient agar plates and were confirmed with mPCR to identify virulence markers stx 1 , stx 2 , eaeA , and ehxA genes. Serotyping was done using conventional serotyping method (Onyeka et al, 2020; Ørskov & Ørskov, 1984).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation